Exploring Augmented Reality for Dental Implant Surgery: Feasibility of Using Smartphones as Navigation Tools - Richard Mosch; Vasilios Alevizakos; Dragan Alexander Ströbele; Marcus Schiller; Constantin vonSee (Clinical and Experimental Dental Research)
ABSTRACT Objectives Dental implant placement requires exceptional precision to ensure functional and esthetic success. Traditional guidance methods, such as static drilling guides and dynamic navigation systems, have improved accuracy but are limited by high costs, rigidity, and reliance on specialized hardware. This study introduces an augmented reality (AR) system using consumer smartphones for real‐time navigation in dental implant placement. The system aims to provide a cost‐effective, eco‐friendly alternative to conventional methods by integrating virtual planning with physical models. Material and Methods A modified dental training model with removable parallel pins served as the physical component. Implant positions were digitally planned and color‐coded using 3D scanning and modeling software, then integrated into an AR application built with Unity Engine. A smartphone's camera was calibrated to project virtual overlays onto the physical model. In vitro testing evaluated alignment accuracy, drill guidance, and system performance under controlled lighting conditions. Results The AR system successfully aligned virtual overlays with the physical model, providing effective visual guidance for implant drill positioning. Operators maintained planned trajectories, demonstrating the feasibility of AR as an alternative to static and dynamic guidance systems. Challenges included the system's sensitivity to stable lighting and visual cues. Conclusions This AR‐based approach offers an accessible and sustainable solution for modern dental implantology. Future research will focus on quantitative accuracy assessments, AI integration for enhanced performance, and clinical trials to validate real‐world applicability. AR technology has the potential to transform dental practices by improving outcomes while reducing costs and environmental impact.